حلال ای-کامریس، اسلامی اصول تجارت کی روشنی میں ایمیزون ایف بی اے کا علمی جائزہ: Halal E-Commerce, Reviewing Amazon FBA Against Shariah-Compliant Trade Principles (Khairulummah, 2025)
In the era of rapidly expanding digital marketplaces, e-commerce plays a pivotal role in transforming traditional trade dynamics. From “Brick and mortar store” to the trends of “Online seller central accounts” the journey is exceptional. Among the most dominating platforms, Amazon, in general, and its FBA model, in particular, remains on the top. This model allows a seller to store, market and distribute the products via vast Amazon’s infrastructure. This research critically examines the FBA model considering Islamic Trading Principles aiming to assess its compatibility with Shariah guidelines for halal business conduct.The study begins by exploring the principles of Islamic commercial Jurisprudence, such as transparency, mutual consent, prohibition of Riba and Gharar, avoidance of uncertainty and artificial risks and ethical treatment of consumers derived from Quranic injunctions, Hadith literature and classical Fiqh. Further, the research incorporates modern interpretations and Fatwas from contemporary Islamic Finance Scholars to address the evolving business structure.The Amazon FBA system is then analyzed through Islamic Principles: the nature of contracts between seller and Amazon(aqd), possession(qabd), warehousing arrangements (Amanah or Ijarah), costumer return policy(khiyar), and commission structures.Findings suggests that Amazon FBA platform may be in parallel with Shariah-compliant model, various elements may require careful structuring. For instance, ensuring halal product listings, transparency in product representation, avoidance of exploitative pricing and misleading promotions.The paper portrays the recommendations from Muslim entrepreneurs, Islamic Finance Scholars and Institutions in such regards. It also highlights the need of Ijtihad (independent reasoning) to address the complexities of modern trade while preserving the spirit of Islamic Finance principles.